Advances in the diagnosis, pathogenesis and treatment of neuropsychiatric systemic lupus erythematosus. Issue 2 (March 2020) - Moore, Erica; Huang, Michelle W.; Putterman, Chaim
Abstract : Purpose of review: Diagnosing and treating neuropsychiatric systemic lupus erythematosus (NPSLE) remains challenging as the pathogenesis is still being debated. In this review, we discuss studies evaluating recent advances in diagnostic methods, pathogenic mediators and potential treatments. Recent findings: Screening tools used for neurodegenerative diseases were found to be both sensitive and moderately specific for cognitive dysfunction in NPSLE. Neuroimaging can be used to distinguish systemic lupus erythematosus (SLE) patients from healthy controls, but further refinement is needed to differentiate between lupus patients with and without neuropsychiatric manifestations. Elevated levels of specific molecules in the cerebrospinal fluid and/or serum, as well as the presence of certain autoantibodies, have been identified as potential biomarkers in attempts to facilitate a more accurate and objective diagnosis. Among such autoantibodies, anti-NR2 and anti-ribosomal P autoantibodies also have a pathogenic role, although newer studies demonstrate that blood–brain barrier damage may not always be required as previously believed. These and other observations, together with new evidence for disease attenuation after microglial modulation, suggest direct involvement of the central nervous system in NPSLE pathogenesis. Summary: Neuropsychiatric involvement of SLE includes a variety of symptoms that impact quality of life and patient prognosis. There have been recent advances in improving the diagnosis of NPSLE as well as in dissecting the underlying pathogenesis. The attenuation of neuropsychiatric disease in mouse models demonstrates the potential for targeted therapies, which are based on a clearer understanding of the pathogenesis of NPSLE. Further assessment of these treatments is required in NPSLE patients, as well as the potential use of neuroimaging to distinguish between SLE patients with or without neuropsychiatric manifestations.